Acupuncture versus sham acupuncture for simple obesity: a systematic review and meta-analysis. Issue 1134 (3rd February 2020) - Zhong, Yu-Mei; Luo, Xiao-Chao; Chen, Yang; Lai, De-Li; Lu, Wen-Ting; Shang, Ya-Nan; Zhang, Lin-Lin; Zhou, Hai-Yan
Abstract: Obesity is a growing chronic health problem worldwide. Studies about acupuncture for obesity treatment are many. But there are some doubts about the effectiveness of acupuncture versus sham acupuncture in treating obesity due to its lack of medical evidence. Therefore, the aim of this study is to assess the efficacy of acupuncture for obesity treatment and provide clinic evidence. Four English databases (PubMed, EMBASE, Web of Science and Cochrane Central Register of Controlled Trials) and four Chinese databases (China National Knowledge Infrastructure, Chinese BioMedical Database, Chinese Scientific Journal Database and Wan-Fang Data) were searched from their receptions to August 2019. Randomized controlled trials (RCTs) using the comparison between acupuncture and sham acupuncture to treat simple obesity were included. The primary outcome of body mass index (BMI) would be used to measure the effect of acupuncture on obesity. According to the trial data extraction form based on the Cochrane Handbook, two reviewers separately extracted the data. Risk of bias of the RCTs was assessed by the Cochrane Risk of Bias Tool. The study included 8 RCTs with 403 patients. When compared with sham acupuncture, acupuncture showed obviously effect in BMI reduction (MD=1.0kg/m2, 95% CI=0.6 to 1.4, P<0.001). There was also significant reduction in body weight (MD=1.85kg, 95%CI=0.82 to 2.88, p<0.001), WC (MD=0.97cm, 95%CI=0.24 to 1.71, p=0.01) and body fat mass percentage (MD=1.01, 95%CI=0.25 to 1.77, p<0.05). However, WHR (MD=0.01, 95%CI=0 to 0.03, p>0.05) was not statistically and significantly different between the acupuncture and control groups. Adverse effects were reported in 3 studies. The review suggests that acupuncture is an effective therapy for simple obesity rather than a placebo effect. This potential benefit needs to be further evaluated by longer-term and more rigorous RCTs.